Effect of Linseed (Linum usitatissimum) Meal on Productive Traits and Biochemical Blood Constituents of Vanaraja Birds (Indian Journal of Animal Production and Management, 2024)
An experiment was carried out with the  objective of studying the performance of Vanaraja  birds as influenced by the dietary inclusion of  linseed meal by replacing GNC. The study was  conducted with 120 female Vanaraja chicks which  were randomly divided into four groups designated  as T1(control), T2, T3, and T4, and subjected to four  dietary levels of linseed meal by replacing GNC at  the rate of 0%, 4%, 8%, and 12%, respectively. The  birds were reared under deep litter system up to 8  weeks of age and thereafter in cages following  standard management practices. Linseed meal had  a significant effect on the overall mean body weight,  gain in weight, feed intake, and feed conversion  efficiency. The overall mean body weight and gain  in weight was found to be significantly (p
Keywords: Vanaraja birds; linseed meal; body weight; performance index; blood constituents